2016
DOI: 10.1186/s40557-016-0110-7
|View full text |Cite
|
Sign up to set email alerts
|

Long working hours and overweight and obesity in working adults

Abstract: BackgroundPrevious studies have identified a link between gender and the various risk factors associated with obesity. We examined obesity risk factors in working adults to identify the effects of differences in body mass index (BMI) and percentage body fat (PBF) between women and men.MethodsA total of 1,120 adults agreed to participate in the study. Data from 711 participants, including 411 women and 300 men, were analyzed. Multiple logistic regression analysis was used to estimate the effects of risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…In a study conducted in Australia with a total of 9276 working women aged 45-50 years, the rate of weight gain increased as the number of working hours increased and the association between the number of working hours and weight gain was stronger in higher percentiles of the weight gain distribution [38]. A study conducted in Korea reported that the likelihood of overweight or obesity increased by 3.82 times among women aged >50 years and working for ≥9 h per day compared with women younger than 50 years and working for <9 h, whereas this was not significant among men [39]. These previous study findings support our findings.…”
Section: Discussionmentioning
confidence: 96%
“…In a study conducted in Australia with a total of 9276 working women aged 45-50 years, the rate of weight gain increased as the number of working hours increased and the association between the number of working hours and weight gain was stronger in higher percentiles of the weight gain distribution [38]. A study conducted in Korea reported that the likelihood of overweight or obesity increased by 3.82 times among women aged >50 years and working for ≥9 h per day compared with women younger than 50 years and working for <9 h, whereas this was not significant among men [39]. These previous study findings support our findings.…”
Section: Discussionmentioning
confidence: 96%
“…B. Kim et al 2016) zu. Zudem sind Schlafprobleme und psychische Beschwerden wie Depressionen oder Burnoutsymptome mit langen Arbeitszeiten assoziiert (z.…”
Section: Stand Der Forschung Und Fragestellungenunclassified
“…Besides knowing the obesity prevalence rates for the different worker categories, it is also important to understand the reasons for them, in other words to identify the work-related factors (besides sedentary work, jobs with low physical demand, nutrition at work) that could possibly be associated with obesity. Subjects who worked long hours had a high risk of overweight/obesity (35,40); similarly, working ≥35 and >40 or >50 hours per week was significantly associated with increased BMI in men (41) and with obesity in workers of both sexes (22,38), whereas Kim et al (36) found an association between this condition and long working hours only in women workers. We found no significant association between long working hours and overweight or obesity, even though women who worked >40 and ≥55 hours/week had the highest prevalence of overweight and obesity, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have looked further into this topic, seeking correlations between the obesity prevalence and some specific occupational factors or work organization characteristics. Associations were found with working hours, shift work, hostile work environment, sedentary work and low physical demand, company size (21,22,(33)(34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 97%